1999
DOI: 10.1073/pnas.96.10.5458
|View full text |Cite
|
Sign up to set email alerts
|

From HER2/Neu signal cascade to androgen receptor and its coactivators: A novel pathway by induction of androgen target genes through MAP kinase in prostate cancer cells

Abstract: Overexpression of the HER2͞Neu protooncogene has been linked to the progression of breast cancer. Here we demonstrate that the growth of prostate cancer LNCaP cells can also be increased by the stable transfection of HER2͞Neu. Using AG879, a HER2͞Neu inhibitor, and PD98059, a MAP kinase inhibitor, as well as MAP kinase phosphatase-1 (MPK-1), in the transfection assay, we found that HER2͞Neu could induce prostate-specific antigen (PSA), a marker for the progression of prostate cancer, through the MAP kinase pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
358
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(377 citation statements)
references
References 31 publications
16
358
1
2
Order By: Relevance
“…23 Increased PSA levels following treatment with other signal transduction modifiers has also been observed in other preclinical models. For example, while HER2/neu has been demonstrated to induce AR transactivation, stabilize AR protein levels and optimize binding of AR to promoter/enhancer regions, 24,25 the HER2/neu inhibitor Herceptin, was shown to markedly increase PSA levels/gram of tumor in LNCaP and CWR22R prostate cancer xenografts. 26 In addition, Korkmaz et al demonstrated that the histone deacetylase inhibitors trichostatin A, depsipeptide and sodium butyrate can enhance AR transcriptional activity in LNCaP cells leading to increased production of PSA.…”
Section: Discussionmentioning
confidence: 99%
“…23 Increased PSA levels following treatment with other signal transduction modifiers has also been observed in other preclinical models. For example, while HER2/neu has been demonstrated to induce AR transactivation, stabilize AR protein levels and optimize binding of AR to promoter/enhancer regions, 24,25 the HER2/neu inhibitor Herceptin, was shown to markedly increase PSA levels/gram of tumor in LNCaP and CWR22R prostate cancer xenografts. 26 In addition, Korkmaz et al demonstrated that the histone deacetylase inhibitors trichostatin A, depsipeptide and sodium butyrate can enhance AR transcriptional activity in LNCaP cells leading to increased production of PSA.…”
Section: Discussionmentioning
confidence: 99%
“…45 This has been shown to occur in vivo in a cell-line model where HER2/neu regulates the phosphorylation of AR through a MAP kinase pathway. 46,47 IL-6 can also activate AR in the absence of androgen. 48 has been shown to act through Ser/Thr kinase Pim-1 and tryrosine kinase Ekt.…”
Section: Amplification Of the Armentioning
confidence: 99%
“…HER2/neu belongs to the EGFR family of receptor tyrosine kinases and has been implicated in androgen-independent prostate cancer growth by activation of the androgen receptor pathway. 70,71 The HER2/neu pathway also promotes cell survival through the PI-3/Akt pathway 72 by inactivating the pro-apoptotic protein Bad. 73 Interestingly, the PI-3/ Akt pathway activates the NF-kB transcription factor which mediates several cellular processes including cell growth, inflammatory responses and apoptosis 63 and inhibition of TGF-b signaling by increasing Smad7 expression.…”
Section: (3) Antagonistic Signaling Pathways Of Tgf-b Mediated Apoptomentioning
confidence: 99%